Efisiensi Ekonomis dan Teknis Usaha Tani Singkong pada Kelompok Tani di Desa Banteran, Sumbang, Kabupaten Banyumas dan di Desa Selakambang, Kaligondang, Kabupaten Purbalingga, 2010 - Agus Arifin; Oke Setiarso (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2010)
The purposes of this study are to analyze the effect of labor, land, seed, fertilizer, and capital on the production of cassava; to analyze the economic efficiency and technical efficiency in cassava farming between farmer groups in Banyumas and Purbalingga; and to analyze the difference of economic and technical efficiencies of cassava farming in Banyumas and Purbalingga. This research is conducted with qualitative and quantitative analysis based on production function with a stochastic frontier approach (Stochastic Frontier Production Function): regression analysis, maximum likelihood (MLE), the analysis of technical efficiency(DEA), economic efficiency, price efficiency, and Return-Cost (R/C) ratio. The result shows there are only three significant independent variables namely labor, land, and capital. Based on analysis of technical efficiency (ET), there are only ten efficient farmers in Banyumas and four efficient farmers in Purbalingga. The results from the efficiency of the price and economic efficiency show that the farming of cassava has no efficient in both of farmer groups in Banyumas and Purbalingga. From the calculation of technical efficiency, price efficiency, and economic efficiency, it can be concluded that cassava farming has no efficient. The results from R/C ratio indicate that cassava farming in both of them are quite profitable. Keyword: economic efficiency, efficiency price, return-cost ratio, stochastic frontier, technical efficiency